Training of street vendors of ready-to-eat chicken in Ouagadougou on best practices in hygiene using a food safety champion approach - Dione, Michel M.; Ilboudo, Guy S.; Madjdian, D.; Badu, V.D.; Asseldonk, M. van; Snoek, H.; Tacken, G.; Kagambèga, A.; Lallogo, Valérie R.; Knight-Jones, Theodore J.D. (International Livestock Research Institute, 2023)
Objective The Pull-Push project “Urban food markets in Africa: Incentivizing food safety using a pull-push approach” strives to sustainably reduce the burden of foodborne disease by improving the food safety of fresh foods sold within urban informal markets in Burkina Faso by adopting the Pull-Push approach. This approach utilizes a behavior change strategy to impact two aspects of the food system. First, to understand if consumer demand can provide an incentive for value chain actors to improve food safety in low and middle-income countries (“Pull”). A large consumer awareness campaign was conducted attempting to generate this consumer demand for safer food. Secondly, we provided capacity building to vendors and regulators to improve current food safety practices (“Push”). Here we report the project’s experience of using a participatory stakeholder engagement approach to train chicken meat vendors in Ouagadougou. Materials and Methods We used a training of trainers (ToT) approach through empowerment of Food Safety Champions (FSC). The FSC were selected from the national food safety regulatory bodies and mentored by the project team of experts in food safety. The training package was built from evidence on how to improve food safety that have been documented during the project’s value chain assessment, knowledge attitude and practices surveys as well as during several national food safety stakeholder engagement meetings. The training content was linked to the messages in the consumer awareness campaigns on best practices for safe food which was implemented at the same time by an advertising agency. A participatory approach was used to deliver the training to food handlers. We used small group discussions, room lectures, demonstrations, case stories and brainstorming. The aids were made of posters, pictures, leaflets, audios, and videos. Inexpensive, renewable food safety equipment was supplied to training beneficiaries. This included disinfectants, protective clothing, basins, a chopping board and a dust bin. Finally, at the end of the training, a certificate of attendance was provided to participants. The perception of the beneficiaries about the usefulness of the training was assessed immediately at the end of the training. Results The training was implemented from 28 October to 26 November 2022 and each session lasted three days with 4 to 5 hours/day. In total, 75 chicken outlets owners and their employees were trained separately in small groups of 20 participants. For most participants, the training was a new experience. Participants were interested in all training sessions, but particularly the practical demonstrations e.g. hand washing, microbial growth on petri-dishes. They appreciated the food safety equipment provided, as well as the certificate of attendance, which is perceived as a reward for pride in their working environment. The participants plan to implement the knowledge learned and some have planned to train their peers or employees who have not been able to benefit from the training. Conclusion The feedback from the participants was overall very positive with a commitment made by them to improve their practices. The knowledge gained by chicken processors on good hygienic practices will contribute to reducing contamination of chicken meat and the food safety risk to consumers. Medium and long-term change measurement are planned at three months after training and beyond, in a randomized-controlled trial, with controls then receiving the training at the end of the trial.